HSV-1\EGFP stimulates miR-146a expression in a NF-κB-dependent manner in monocytic THP-1 cells - Venuti, Assunta (Sci Rep, 2019)
The nuclear factor κB (NF-κB) pathway plays a key role in innate and adaptive immunity, cell proliferation and survival, inflammation and tumors development. MiR-146a is an immune system regulator that has anti-inflammatory function in multiple cell types and conditions. Here we demonstrate activation of canonical NF-κB pathway in monocytic cells upon HSV-1 replication. By constructing and using a recombinant HSV-1\EGFP virus, we monitored the capability of the virus to recruit NF-κB and we report that the phosphorylation of p65 protein correlates with an active virus replication at single-cell level. In addition, we found that upregulation of miR-146a during viral replication is strictly dependent on NF-κB activation and correlates with tight control of the interleukin-1 receptor-associate kinase 1 (IRAK1). Accordingly, THP-1 DN IκBα cells, expressing a dominant negative mIκBα, did not show upregulation of miR-146a upon HSV-1 infection. Our data suggest that the expression of miRNA-146a modulates NF-κB activation through targeting IRAK1 during HSV-1 replication in THP-1 cells.